Enhancing Biotechnology Learning Through PRA-Driven Hydroponic Technology - Saidah Oktariyati; Yulia Safitri; Kardina Engelina Siregar (Al-Qalam Institue, 2026)
This study aims to investigate the application of appropriate hydroponic technology as a learning tool in biotechnology education, focusing on its impact on students’ theoretical understanding, practical skills, and collaborative abilities. The study employed socialization and mentoring based on Participatory Rural Appraisal (PRA) to actively involve students in the learning process. Data were collected through literature review and structured observations, then analyzed qualitatively to identify key outcomes and patterns. The results indicate that integrating hydroponic technology in biotechnology education effectively enhances students’ comprehension of concepts while providing hands-on experience. Students demonstrated increased independence, improved peer collaboration, and the ability to implement environmentally friendly and efficient planting practices. Moreover, the approach facilitated the development of adaptive and sustainable problem-solving skills. These findings suggest that appropriate hydroponic technology can serve as an innovative and practical pedagogical tool in biotechnology education, fostering both cognitive and experiential learning. Future research is recommended to explore long-term impacts on student performance and to refine the integration of PRA-based methods in science curricula.